2021
DOI: 10.1021/acs.inorgchem.1c01397
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Ag Complex Modified Keggin-Type Coordination Polymers for Improved Electrochemical Capacitance, Dual-Function Electrocatalysis, and Sensing Performance

Abstract: Different metal−organic units were introduced into the {PMo 12 } polyoxometalate (POM) system to yield three porous coordination polymers with distinct characteristics, {Cu(pra) 2 } [{Cu-(pra) 2 } 3 {PMo 11 VI Mo V O 40 }] (1), [{Ag 5 (pz) 6 (H 2 O) 0.5 Cl}{PMo 11 VI Mo V O 40 }] (2), and [{Cu 3 (bpz) 5 (H 2 O)}{PMo 12 O 40 }](3) (pra = pyrazole; pz = pyrazine; bpz = benzopyrazine), via an in situ hydrothermal method. In comparison with the maternal Keggin cluster and most reported POM electrode materials, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 80 publications
(83 reference statements)
0
21
0
Order By: Relevance
“…The C s values were 823.8, 740.0, 631.3, 500.0, 431.3, and 350 F g –1 for the 2 -GCE, 798.8, 732.5, 656.3, 562.5, 487.5, and 425.0 F g –1 for 3 -GCE at the same current densities as those for the 1 -GCE. For BOHU-1 and BOHU-3 , their different capacitance performances can be attributed to different POMs and their different distinct structures . In BOHU-3 , the MnMo 9 anions could expose more active sites to enhance the capacitance and rate performance (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C s values were 823.8, 740.0, 631.3, 500.0, 431.3, and 350 F g –1 for the 2 -GCE, 798.8, 732.5, 656.3, 562.5, 487.5, and 425.0 F g –1 for 3 -GCE at the same current densities as those for the 1 -GCE. For BOHU-1 and BOHU-3 , their different capacitance performances can be attributed to different POMs and their different distinct structures . In BOHU-3 , the MnMo 9 anions could expose more active sites to enhance the capacitance and rate performance (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…For BOHU-1 and BOHU-3, their different capacitance performances can be attributed to different POMs and their different distinct structures. 21 In BOHU-3, the MnMo 9 anions could expose more active sites 22 to enhance the capacitance and rate performance (Figure 4c). For BOHU-1 and BOHU-2, different metal ions have a greater influence on the electrochemical storage capacity.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…One of the merits of POM-incorporated metal-organic networks is that they can be easily tailored by a judicious choice of metal ions, bridging organic ligands and polyanions. 30 Numerous studies reported that transition metal (TM) ions (Co, Zn, etc.) can act as catalytic centers for various oxidation processes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Zhou's group has reported three POMOCs containing Keggin-type polyoxometalates, in which complex 2 exhibited excellent sensing and detection properties for H 2 O 2 and AA. 27 Bromate (KBrO 3 ) and nitrite (KNO 2 ) can be used as food additives and preservatives, respectively, but excessive consumption will cause great harm to the human body. 28–30 Therefore, their control and detection are necessary.…”
Section: Introductionmentioning
confidence: 99%